Calculation of Roofing Three-Layer Sandwich Panels - Kahorovich, Rakhimov Akram; Kobilovich, Turobov Shakhram (European Journal of Life Safety and Stability (2660-9630), 2022)
The article presents three-layer sandvich panels aswell as information. The constructive solutions of the panels and the basics of theoretical calculations are described.